2020
DOI: 10.4049/jimmunol.2000037
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of NK Cells Improves Cognitive Function in the Alzheimer Disease Mouse Model

Abstract: Despite mounting evidence suggesting the involvement of the immune system in regulating brain function, the specific role of immune and inflammatory cells in neurodegenerative diseases remain poorly understood. In this study, we report that depletion of NK cells, a type of innate lymphocytes, alleviates neuroinflammation, stimulates neurogenesis, and improves cognitive function in a triple-transgenic Alzheimer disease (AD) mouse model. NK cells in the brains of triple-transgenic AD mouse model (3xTg-AD) mice e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 63 publications
3
54
0
Order By: Relevance
“…Neutrophil depletion or suppression of neutrophil trafficking ameliorated memory impairment in 3xTg-AD transgenic mice (5). Depletion of NK cells by anti-NK1.1 antibody enhanced neurogenesis, reduced neuroinflammation, and ameliorated cognitive impairment in 3xTg-AD mice (7). These studies have confirmed the interaction between peripheral immune cells and the CNS in AD.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Neutrophil depletion or suppression of neutrophil trafficking ameliorated memory impairment in 3xTg-AD transgenic mice (5). Depletion of NK cells by anti-NK1.1 antibody enhanced neurogenesis, reduced neuroinflammation, and ameliorated cognitive impairment in 3xTg-AD mice (7). These studies have confirmed the interaction between peripheral immune cells and the CNS in AD.…”
Section: Introductionmentioning
confidence: 60%
“…The cytotoxic activity of peripheral NK cells is impaired in aged individuals compared to that in young adults during aging (30). Circulating NK cell infiltration into the brain has been found in human AD and 3xTg-AD mice (6,7). NK cells exhibited enhanced pro-inflammatory profiles in the brains of 3xTg-AD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Ly6C + monocytes and Ly6G + neutrophils were sorted by FACS. scRNA‐seq was performed as we previously described (Fung et al, 2020 ; Harly et al, 2019 ; Zhang et al, 2020 ). scRNA‐seq libraries were generated using the chromium 5’ single‐cell gene expression kit (10x genomics) according to the manufacturer's instructions.…”
Section: Discussionmentioning
confidence: 99%
“…scRNA-seq was performed as we previously described [ 5 , 18 , 29 ]. Specifically, single-cell libraries were generated using Chromium 5” gene expression (10x Genomics) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…CD8 + effector memory T cells with enhanced T cell receptor (TCR) signaling accumulated in the brains of AD patients, and their numbers were negatively associated with cognitive function [ 4 ]. Depletion of NK cells, the innate lymphocyte subset with cytotoxic function, alleviated neuroinflammation and cognitive decline in the triple transgenic mouse model of AD (3xTg-AD) [ 5 ]. Nevertheless, genetic deletion of both adaptive and innate lymphocytes led to exacerbated Aβ pathology in 5xfAD mice, indicating that some other lymphocyte subsets might instead play a protective role in AD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%